Comparative study of automatic and manual planning methods for volumetric modulated arc therapy in patients with intraocular cancer. Issue Volume 4:Issues 3(2020) (23rd September 2020) - Zheng, Xiaomin; Han, Ce; Yi, Jinling; Zhou, Yongqiang; Ai, Yao; Xie, Congying; Jin, Xiance
Abstract: Objective: To research and assess automatic volumetric modulated arc therapy (VMAT) planning methods for patients with intraocular cancer. Methods: The mdaccAutoPlan system was added to the Pinnacle 3 treatment planning system as a plug‐in. Automatic VMAT plans were generated for 10 patients diagnosed with intraocular cancer, and evaluated according to standard dose‐volume histogram parameters. Results: The planning target volume of enrolled patients ranges from 14.24 to 50.69 cm 3 . Both planning methods lead to acceptable planning target volume target coverage with a V95 of 97.9 ± 1.4% and 96.4 ± 1.5% for manual and automatic plans ( P  = 0.03), respectively. Automatic planning lowered the dose delivered to the ipsilateral lens and optical nerves, but increased the dose to the brainstem compared with manual planning. Automatic planning significantly prolonged VMAT planning time (3.25 ± 0.53 h vs. 1.02 ± 0.69 h, P  < 0.01), but no significant differences were seen in average machine units (474.0 ± 64.8 vs. 502.4 ± 109.5, P  = 0.34) compared with the manual planning method. Conclusions: Automatic VMAT planning achieved acceptable target coverage, and lowered the dose delivered to ipsilateral lens and brainstem in patients with intraocular cancer compared with manual planning. However, the full benefits of automatic VMAT planning require further study with improved performance and treatment planning system capacity.